Visuomotor performance at high altitude in COPD patients. Randomized placebo-controlled trial of acetazolamide - Scheiwiller, P. M.; Furian, M.; Buergin, A.; Mayer, L. C.; Schneider, S. R.; Mademilov, M.; Lichtblau, M.; Muralt, L.; Sheraliev, U.; Sooronbaev, T. M.; Ulrich, S.; Bloch, K. E. (Frontiers in Physiology, 2022)
Introduction We evaluated whether exposure to high altitude impairs visuomotor learning in lowlanders with chronic obstructive pulmonary disease (COPD) and whether this can be prevented by acetazolamide treatment. Methods 45 patients with COPD, living <800 m, FEV1 ≥40 to <80%predicted, were randomized to acetazolamide (375 mg/d) or placebo, administered 24h before and during a 2-day stay in a clinic at 3100 m. Visuomotor performance was evaluated with a validated, computer-assisted test (Motor-Task-Manager) at 760 meters above sea level (baseline, before starting the study drug), within 4h after arrival at 3100 m and in the morning after one night at 3100 m. Main outcome was the directional error (DE) of cursor movements controlled by the participant via mouse on a computer screen during a target tracking task. Effects of high altitude and acetazolamide on DE during an adaptation phase, immediate recall and post-sleep recall were evaluated by regression analyses. www.ClinicalTrials.gov NCT03165890. Results In 22 patients receiving placebo, DE at 3100 m increased during adaptation by mean 2.5°, 95%CI 2.2° to 2.7° (p<0.001), during immediate recall by 5.3°, 4.6° to 6.1° (p<0.001), and post-sleep recall by 5.8°, 5.0 to 6.7° (p<0.001), vs. corresponding values at 760 m. In 23 participants receiving acetazolamide, corresponding DE were reduced by -0.3° (-0.6° to 0.1°, p=0.120), -2.7° (-3.7° to -1.6°, p<0.001) and -3.1° (-4.3° to -2.0°, p<0.001), compared to placebo at 3100 m. Conclusions Lowlanders with COPD travelling to 3100 m experienced altitude-induced impairments in immediate and post-sleep recall of a visuomotor task. Preventive acetazolamide treatment mitigated these undesirable effects.